2005
DOI: 10.1055/s-2005-915635
|View full text |Cite
|
Sign up to set email alerts
|

Fully Endoscopic Endonasal vs. Transseptal Transsphenoidal Pituitary Surgery

Abstract: A long-term retrospective study of 300 patients who underwent fully endoscopic endonasal pituitary adenoma resection between November 1998 and October 2004. The patients' records as well as the data obtained from postoperative follow-up visits was used to determine outcomes. Additionally, the data were then compared to mean values calculated from several transseptal-transsphenoidal reports. From a total of 300 pituitary adenomas, 139 (46 %) were hormonally active, while 161 (54 %) were non-functioning. Mean fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
101
4
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 23 publications
(30 reference statements)
8
101
4
6
Order By: Relevance
“…The remission rate of hypersecretion was significantly better in the endoscopic group (63 vs 50%). Kabil et al reported on 300 pts undergoing endoscopic resection with a similar cure rate of 87% in GH secreting adenomas, 86% in Cushing's disease and 80% in prolactinomas (Kabil et al, 2005). We have also noted a high cure rate in our endoscopic series of patients treated for Cushing's disease (figure 8a&b).…”
Section: Endoscopic Endonasal Surgery: Advantagessupporting
confidence: 60%
See 1 more Smart Citation
“…The remission rate of hypersecretion was significantly better in the endoscopic group (63 vs 50%). Kabil et al reported on 300 pts undergoing endoscopic resection with a similar cure rate of 87% in GH secreting adenomas, 86% in Cushing's disease and 80% in prolactinomas (Kabil et al, 2005). We have also noted a high cure rate in our endoscopic series of patients treated for Cushing's disease (figure 8a&b).…”
Section: Endoscopic Endonasal Surgery: Advantagessupporting
confidence: 60%
“…O'Malley et al reported on 50 pts, half of them undergoing microscopic approaches and half undergoing endoscopic approaches, and showed comparable complication rates between the two groups for both CSF leak and incidence of diabetes insipidis with a trend toward less diabetes incipidus (DI) in the endoscopic group (O'Malley et al, 2008) . Kabil et al demonstrated a 2% CSF leak in a series of over 650 patients undergoing endoscopic resection (Kabil et al, 2005). Minor complications include septal perforation, trauma to external nose and sinusitis.…”
Section: Complications and Disadvantagesmentioning
confidence: 99%
“…In these series, cure rates range from 57% to 100%. 7,10,13,21,22,27,31,33,34,44,57,66 We are aware of only one early study that focused specifically on outcomes after endoscopic resection in the setting of acromegaly. 44 In this early study the authors reviewed the cases of 5 patients with mostly microadenomas and reported a cure rate of 100% using a liberal cure benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…The application of endoscopes in transsphenoidal surgery in the 1990s changed this situation, because the lenses provided a wider field of view. 11,15,36,39,60 This wider view enables the surgeon to inspect the medial wall of the CS directly and therefore to pass a more reliable judgment regarding parasellar invasiveness.…”
mentioning
confidence: 99%
“…52,62 Overt parasellar invasion into cavernous sinus (CS) structures is found intraoperatively in 6%-10% 1,20 of cases and is the most important reason for incomplete resection and the decrease in cure rates from 78%-92% (in cases without parasellar invasion) to 20%-52%. 16,20,21,24,36,39,62,64 Because of the close relationship of the internal carotid arteries (ICAs), histological specimens of the medial wall are not routinely available, 54,65,77 so surgical observations 59 and/or radiological signs of invasion 14 are still the most important methods of detection.…”
mentioning
confidence: 99%